Highly emissive organic solids with remarkably broad color tunability based on N,C-chelate, four-coordinate organoborons - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T. (Chemical Communications, 2015)
Molecular fluorophores based on N,C-chelate, four-coordinate organo-borons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au(I)/Au(III)-catalysis: discovery of pyridinium-oxazole dyad as novel lonic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie International Edition, 2016)

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au-I/Au-III catalysis: discovery of a pyridinium-oxazole dyad as an ionic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie-International Edition, 2017)
Oxidative intramolecular 1,2-amino-oxygenation reactions, combining gold(I)/gold(III) catalysis, is reported. The reaction provides efficient access to a structurally unique ionic pyridinium-oxazole dyad with tunable emission wavelengths. The application of these fluorophores as potential biomarkers has been investigated.

Ionic pyridinium-oxazole dyads: design, synthesis, and application in mitochondrial imaging - Shaikh, Aslam C.; Varma, Mokshada E.; Mule, Ravindra D.; Banerjee, Somsuvra; Kulkarni, Prasad P.; Patil, Nitin T. (Journal of Organic Chemistry, 2019)
We recently developed an oxidative intramolecular 1,2-amino-oxygenation reaction, combining gold(I)/gold(III) catalysis, for accessing structurally unique ionic pyridinium-oxazole dyads (PODs) with tunable emission wavelengths. On further investigation, these fluorophores turned out to be potential biomarkers; in particular, the one containing -NMe2 functionality (NMe2-POD) was highly selective for mitochondrial imaging. Of note, because of mitochondria's involvement in early-stage apoptosis and degenerative conditions, tracking the dynamics of mitochondrial morphology with such imaging technology has attracted much interest. Along this line, we wanted to build a library of such PODs which are potential mitochondria trackers. However, Au/Selecfluor, our first-generation catalyst system, suffers from undesired fluorination of electronically rich PODs resulting in an inseparable mixture (1:1) of the PODs and their fluorinated derivatives. In our attempt to search for a better alternative to circumvent this issue, we developed a second-generation approach for the synthesis of PODs by employing Cu(II)/PhI(OAC)(2)-mediated oxidative 1,2-amino-oxygenation of alkynes. Thes newly synthesized PODs exhibit tunable emissions as well as excellent quantum efficiency up to 0.96. Further, this powerful process gives rapid access to a library of NMe2-PODs which are potential mitochondrial imaging agents. Out of the library, the randomly chosen POD-3g was studied for cell-imaging experiments which showed high mitochondrial specificity, superior photostability, and appreciable tolerance to microenvironment changes with respect to commercially available MitoTracker green.

`Turning on' to glutathione: a rhodamine-based fluorescent chemodosimeter with nanomolar sensitivity - Badekar, Pooja S.; Deo, Harshada S.; Varma, Mokshada E.; Kulkarni, Prasad P.; Maibam, Ashakiran; Krishnamurty, Sailaja; Kumbhar, Anupa A. (ChemistrySelect, 2024)
A new colorimetric and fluorescence turn-on chemodosimeter for selective detection of GSH over Cys and Hcy with 34-fold enhancement in emission intensity is reported. Probe 1 exhibited ultra-sensitivity toward GSH with 0.125 nM detection limit and successfully displayed GSH detection in MCF-7 live cells. The mechanism of sensing is established by density functional theoretical calculations.
Keywords: Chemodosimeter; Fluorescence turn-on; GSH; MCF-7 cells; Rhodamine